Le temps suspendu (Maison des Sciences de l'homme d'Aquitaine, 2023)
In Raymond Radiguet’s works, women confronted with the absence of their spouse are a recurrent literary figure. Between the virtuous wife set up as a model and the adulterous woman who is a source of scandal, there are many nuances that encourage us to go beyond this reductive approach. Suspended time’ is precisely a window on the history of married women confronted with the long-term absence of a husband, considering them in their full agentivity and not as victims undergoing the throes of separation. The question of the autonomy and independence of wives in Western societies, which have long been patriarchal, is therefore at the heart of this book. Indeed, the departure of men, whether they are at war, at sea or elsewhere, offers the possibility of partially bypassing the “silences of history” with regard to women and of observing them, on a daily basis, in their confrontation with the absence of the other. This collection of essays is firmly rooted in the history of the family and the history of gender, and offers twenty-four contributions whose approaches alternate between individual trajectories – so many female experiences of absence – and more general perspectives, from Greek antiquity, through Renaissance Italy and revolutionary France, to contemporary Quebec.